Chelating Competency and Antibacterial Properties of (E)-2-((1H-indol-3-yl) metheneamino)-5-bromobenzoic acid and its Metal Chelates - Aby Paul; Joby Thomas K.; Sini Varghese C.; Reeja Johnson (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
Heterocyclic compound (E)-2-((1H-indol-3-yl)metheneamino)-5-bromobenzoic acid (IMABBA) and its Mn(II), Ni(II) and Cu(II) complexes were synthesized and characterized by spectral, elemental, magnetic and conductance measurements. Investigations showed that IMABBA behaved as bidentate ligand during chelation. The octahedral geometry of the chelate was confirmed by magnetic and optical spectral studies. The antibacterial studies of the ligand and metal chelates were evaluated and reported.